Phase velocity and attenuation of longitudinal shear vibrations of hollow poroelastic cylinders - Shah, Ahmed S.; Javvad Hussaini, S. (Zielona Góra: Uniwersytet Zielonogórski)
The present paper is devoted to the study of phase velocity and attenuation of longitudinal shear vibrations of hollow poroelastic circular cylinders in the presence of dissipation. The explicit expressions for phase velocity and attenuation of longitudinal shear vibrations are derived. The frequency equation of longitudinal shear vibrations and modes obtained in a previous paper are used to compute the phase velocity and attenuation for different dissipations for thin and thick poroelastic cylindrical shells and poroelastic solid cylinder.
Keywords: Biot`s theory; hollow cylinder; shear waves; frequency equation; phase velocity; attenuation; wavenumber; dissipation